Analysis for Stiffness Characteristic of Machine Tool Spindle Bearing Under Elastohydrodynamic Lubrication Condition - Hao Yu; Dongchen Qin; Jiangyi Chen; Feng Yuan (Jixie chuandong)
The stiffness characteristics of cylindrical roller bearings will have great impact on the dynamic performance of machine tools. Based on the analysis for the double-row cylindrical roller bearing， considering the influence of the lubricant oil film on the stiffness， the stiffness variation characteristics under different operating conditions and lubrication parameters are analyzed. The analysis results show that the lubricating oil film produced by elastohydrodynamic lubrication will reduce the comprehensive stiffness of the bearing. When the external load increases， the hertz stiffness， the oil film stiffness and the comprehensive stiffness both increase. Increasing the preload value of bearing is conductive to improving the comprehensive stiffness. When the rotation speed increases， the comprehensive stiffness of the bearing shows a downward trend. The increase of the lubricating oil dynamic viscosity coefficient or the pressure viscosity coefficient will both make the comprehensive stiffness of bearing decrease.